Gujarati Aunties on the Integrated Circuit: Internet Infrastructures as an Immigrant Circuit - Dave, Kinjal (AoIR Selected Papers of Internet Research, 2026)
Infrastructures are path dependent. The evolution of the internet at present rely on previously installed historical and analog infrastructures, including highways (Saxenian 1996) and telecommunication lines (Ensmenger 2008). However, the experiences of immigrant communities show that labor pools are also human infrastructures required for the expansion of tech companies (Nakamura 2014, Hossfield 2019, Cowie 2001). Visa restrictions, which operate as a mechanism of racial capitalism (Kelley 2017, Melamed 2015), create an additional layer of path dependency, since migration patterns initially were restricted to highly educated Asians, then later allowed lower-class relatives to migrate on family reunification visas. As part of a larger dissertation project tracing the experience of entrepreneurial identity and migration, this essay examines the overlap between technical and cultural path dependencies to tell the story of one Asian-American diaspora. This project examines the role of one ethno-linguistic network in the domestic manufacturing space – Gujarati-Indians in New Jersey who owned, operated, or worked in electronics factories. Surfacing lessons learned from the legacies of globalization and deindustrialization through immigrant experiences, this project emphasizes the unique cultural relationships built through both professional and working class technical labors among Gujaratis. I argue recounting a near history of immigrant technical work forces us to ask new questions about how the social reproduction of diasporic enclaves is necessary to produce technical laborers in the United States.